2023
DOI: 10.3390/nu15061405
|View full text |Cite
|
Sign up to set email alerts
|

Selenium, Stroke, and Infection: A Threefold Relationship; Where Do We Stand and Where Do We Go?

Abstract: Stroke is currently the second most common cause of death worldwide and a major cause of serious long-term morbidity. Selenium is a trace element with pleotropic effects on human health. Selenium deficiency has been associated with a prothrombotic state and poor immune response, particularly during infection. Our aim was to synthesize current evidence on the tripartite interrelationship between selenium levels, stroke, and infection. Although evidence is contradictory, most studies support the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 139 publications
0
0
0
Order By: Relevance
“…Furthermore, fluctuations in selenium have also been indicated in stroke pathogenesis. The review paper by Liampas et al demonstrated that both excess and decreased levels of selenium and selenoprotein expression can lead to immune and coagulation dysregulation [4]. Selenium has multiple pleiotropic homeostatic roles in human health and mediates its enzymatic functions through selenoproteins, which are known to moderate oxidative stress and coagulation processes such as the arachidonic cascade.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, fluctuations in selenium have also been indicated in stroke pathogenesis. The review paper by Liampas et al demonstrated that both excess and decreased levels of selenium and selenoprotein expression can lead to immune and coagulation dysregulation [4]. Selenium has multiple pleiotropic homeostatic roles in human health and mediates its enzymatic functions through selenoproteins, which are known to moderate oxidative stress and coagulation processes such as the arachidonic cascade.…”
mentioning
confidence: 99%
“…Selenium's protective role in cardiovascular disease has been proven in various studies showing an inverse relationship between low selenium levels and stroke, especially in elder, white, male populations. Furthermore, it has been shown that each 50 µg/L increase in blood selenium and in dietary selenium leads to a 38% and a 30% reduction in the prevalence of stroke, respectively [4]. Selenium supplementation in acute stroke patients has been shown to improve short-term acute stroke outcomes; however, there is limited evidence of its effects on long-term stroke outcomes, and more studies regarding its efficacy and safety must be conducted as selenium excess may cause dysregulation of glucose metabolism in addition to heightened immune activity [4].…”
mentioning
confidence: 99%